Heavy-quark azimuthal momentum correlations as a sensitive probe of thermalization - Tsiledakis, Georgios Karolos; Appelshäuser, H.; Schweda, Kai; Stachel, Johanna (Nuclear physics. A, Nuclear and hadronic physics, 2011)
In high-energy nuclear collisions the degree of thermalization at the partonic level is a key issue. Due to their large mass, heavy quarks and their possible participation in the collective flow of the QCD-medium constitute a powerful probe for thermalization. We present studies with PYTHIA for pp collisions at the top LHC energy of s=14 TeV applying the two-particle transverse momentum correlator 〈Δpt,1,Δpt,2〉 to pairs of heavy-quark hadrons and their semi-leptonic decay products as a function of their relative azimuth. Modifications or even the complete absence of initially existing correlations in Pb+Pb collisions might indicate thermalization at the partonic level.
Gesehen am 17.11.2022